The use of supraclavicular free flap with vascularized lymph node transfer for treatment of lymphedema: A prospective study of 100 consecutive cases. Issue 1 (22nd July 2016) - Mardonado, Andres A.; Chen, Ru; Chang, David W.
Abstract : Background and Objectives: Vascularized lymph node transfer (VLNT) is gaining popularity for treatment of lymphedema. The purpose of this study was to evaluate the flap and the donor site morbidity of the supraclavicular (SC) VLNT. Methods: A review of a prospective database was performed for patients who had undergone SC VLNT to treat upper or lower extremity lymphedema. Flap and donor site complications were registered for each patient. A detailed technical surgical approach is explained. Results: One hundred consecutive patients with lower or upper extremity lymphedema underwent SC VLNT (84% from the right side) with a mean of 11‐months follow‐up (range 3–19 months). There were no flap loss but three flaps (3%) required re‐exploration due to venous congestion of the skin paddle. Two patients had local infection and three patients developed chyle leak (3%) at the donor site but resolved spontaneously. No donor site secondary lymphedema was noted. Conclusions: This is the largest prospective series of SC free flap VLNT for treatment of lymphedema. Low flap and donor site morbidity makes this flap an appealing source of lymph node transfer for lymphedema treatment. J. Surg. Oncol. 2017;115:68–71 . © 2016 Wiley Periodicals, Inc.